Platelet-Rich Plasma: A Review - Ahmad, Muhammad (Current Regenerative Medicine (Discontinued), 2016)
Background: Platelet rich plasma is one of the simplest regenerative medicine method used to deliver growth factors and other substances at the desired areas in higher concentrations. PRP is proved to help in tissue regeneration and augments tissue healing. It is being used in variety of conditions in many surgical and medical conditions. There are multiple commercially available preparation kits which vary in terms of different aspects. However, the vast variations in the clinical settings lack any standardization in preparation, composition and delivery methods. The presence of different cells also influences the outcome of the clinical studies.
Keywords: hair restoration